PENCEGAHAN INFEKSI LUKA POST OPERASI DAN PEMELIHARAAN LINGKUNGAN BANGSAL ANGGREK RS ORTHOPEDI SURAKARTA - Tri Susilowati; Sugiyarto Sugiyarto; Fitriana Andini Putri; As Shafa Nur Khasna; Jihan Naifa Nabilah (Jurnal Padamu Negeri, 2026)
The abstract Surgical site infections (SSIs) are serious complications that can increase morbidity, length of hospital stay, treatment costs, and the risk of disability and death. Education on infection prevention and effective environmental maintenance can prevent these complications. The objective of this activity is to increase patients' and families' knowledge about the signs, symptoms, and prevention methods for infections in postoperative wounds at Dr. Soeharso Orthopedic Hospital in Surakarta. Based on this data, the partner's problem can be formulated as a lack of education, resulting in patients' families not understanding how to prevent surgical site infections. Based on the priority issues agreed upon with the partner, it was agreed to conduct health education activities on the prevention of post-operative wound infections and environmental maintenance for patients and their families. The results showed a significant increase in respondents' knowledge, from 7 people (50%) with insufficient knowledge before the education session to no respondents with insufficient knowledge and 9 people (60%) with good knowledge after the session. Based on the results of the health education activities conducted, 15 respondents at Soeharso Orthopedic Hospital in Surakarta understood the material regarding the definition of infection, signs and symptoms, prevention methods, and the relationship between wound healing and environmental maintenance. After conducting health education on proper nutrition, which was provided directly to patients and their families at Soeharso Orthopedic Hospital in Surakarta.